2002
DOI: 10.1113/jphysiol.2002.025015
|View full text |Cite
|
Sign up to set email alerts
|

Halothane, isoflurane and sevoflurane inhibit NADH: ubiquinone oxidoreductase (complex I) of cardiac mitochondria

Abstract: We have investigated the effects of volatile anaesthetics on electron transport chain activity in the mammalian heart. Halothane, isoflurane and sevoflurane reversibly increased NADH fluorescence (autofluorescence) in intact ventricular myocytes of guinea‐pig, suggesting that NADH oxidation was impaired. Using pig heart submitochondrial particles we found that the anaesthetics dose‐dependently inhibited NADH oxidation in the order: halothane > isoflurane = sevoflurane. Succinate oxidation was unaffected by eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(140 citation statements)
references
References 40 publications
(40 reference statements)
9
127
1
3
Order By: Relevance
“…Although there is no direct evidence that NS-1619 could inhibit mitochondrial function in cardiac cells, we cannot completely rule out the possibility that the cardioprotective effect of this drug is mediated in part through inhibition of complex I of the mitochondrial respiratory chain. In fact, a recent study suggested that the cardioprotective effects of volatile anesthetics (such as halothane, isoflurane, and sevoflu-rane) may be mediated through inhibition of complex I of the cardiac mitochondrial respiratory chain (21). There is also evidence that paxilline inhibits sarco/endoplasmic reticulum Ca 2ϩ -ATPase (SERCA) in vitro (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no direct evidence that NS-1619 could inhibit mitochondrial function in cardiac cells, we cannot completely rule out the possibility that the cardioprotective effect of this drug is mediated in part through inhibition of complex I of the mitochondrial respiratory chain. In fact, a recent study suggested that the cardioprotective effects of volatile anesthetics (such as halothane, isoflurane, and sevoflu-rane) may be mediated through inhibition of complex I of the cardiac mitochondrial respiratory chain (21). There is also evidence that paxilline inhibits sarco/endoplasmic reticulum Ca 2ϩ -ATPase (SERCA) in vitro (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that mitochondria play a vital role in the cardioprotection conferred by volatile anesthetics, the exact target proteins have not been identified. It has long been established that drugs with anesthetic properties have a depressant effect on mitochondrial function (9,11). The slowing of respiration rates at various complexes in the respiratory chain may cause an electron leak and subsequently lead to augmented generation of ROS.…”
mentioning
confidence: 99%
“…29 Fatal halothane rechallenge is widely attributed to immunomediated liver injury with rapid injury with rechallenge, associated fever, eosinophilia, anti-CYP2E1, anti-liver-kidney-microsomal and adduct antibodies, 24,28 and association with HLA A-11. 29 Halothane also causes mitochondrial impairment, due to inhibition of complex I and II, 30 as well as fatty acid and pyruvate oxidation in nonclinical studies. 31 Therefore, halothane's high fatality rate on rechallenge appears related to its combined mitochondrial impairment and immunoallergic injury, most frequently observed with rechallenge occurring within 1 month of initial injury.…”
Section: Resultsmentioning
confidence: 99%